Power management policies and control of hybrid electric vehicle. (29th April 2009) - Srinivasa Rao, Gorantla; Rao, G.K.; Murthy, G.R.K.; Obulesh, Y.
With increasing concern over the environment and ever-stringent emission regulations, the use of hybrid electric vehicle (HEV) is being investigated as an alternative form of transportation. A hybrid vehicle combines the advantages of an electric drive and an internal combustion engine. This paper proposes the necessary hardware and software needed for an effective control of the electrical part of the hybrid vehicle. The controlling functions include stop, start, forward, reverse and speed control. The source of power for the drive can be solar cell or a fuel cell.